(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper presents design, simulation and development of Shunt Hybrid Power Filter (SHPF) for mitigation of the power quality problem at ac mains in ac-dc power supply feeding to a nonlinear load. The power filter is consisting of a shunt passive filter connected with a shunt active power filter. At first passive filter has been designed to compensate harmonics, and then similarly active filter is designed. The drawback associated with the passive filter like fixed compensation characteristics and resonance problem is tried to solve by SHPF.Simulations has been carried out to verify the proposed filter system. Harmonic contents of the source current has been calculated to demonstrate the influence of harmonic extraction circuit on the harmonic compensation characteristic of the shunt hybrid power filter.